Junior High School Students' Skills in Making Posters Through the Blended Li-Pro-GP Learning Model - Yuni Pantiwati*; Deny Fatmawati; Rifqi Yassirul Haqqi (Universitas Syiah Kuala, 2022)
The skill of making a good poster is that it must meet the quality requirements of the poster. A good poster quality consists of clarity of content, completeness of components, aesthetics, composition of text and images. To train students' poster making skills, a supportive learning model is needed. The project based literacy that integrates school literacy movement strengthening character education (Li-Pro-GP) program in the implementation of learning. The purpose of the study was to describe the skills of making posters for junior high school students after using the Li-Pro-GP learning model. The research method uses classroom action research (CAR) at SMPN 23 Malang City, carried out in 2 blended cycles. The results showed that students' skills had increased in making posters based on science concepts. The population of this research is class VII odd semester 2020/2021 students of SMPN 23 Malang. The sample from the research of class VIIC SMPN 23 Malang is 25 students with purposive sampling technique. Data collection with student activity observation sheets includes field notes and poster making skills with poster making indicators. The research data were analyzed descriptively and qualitatively presented with bar and pie charts with an explanation for each percentage on the diagram of the 25 students, it shows that 20% of the students in the very good poster category, 16% of the students in the good category and 64% of the students in the moderate category